134 Acute effects of methadone, buprenorphine or naltrexone on sleep-like parameters evaluated with actigraphy in male rhesus monkeys. (3rd May 2021) - Berro, Lais; Zamarripa, C Austin; Talley, Joseph; Freeman, Kevin; Rowlett, James
Abstract: Introduction: Opioid use disorder (OUD) is a significant public health problem, and it has been associated with the emergence of sleep disturbances. Effective treatment options for OUD exist, including medication-assisted therapy with methadone or buprenorphine. However, emerging evidence suggests that these treatments also may be associated with significant sleep impairment. The extent to which these effects are a result of the medication or an effect of chronic opioid use remains unknown. In the present study, we investigated the acute effects of methadone, buprenorphine or naltrexone in male rhesus monkeys in order to understand whether pharmacological treatment with these drugs per se would have deleterious effects on sleep. Methods: Adult naïve male rhesus macaques (Macaca mulatta, n=5) maintained on a 12h/12h light/dark cycle were fitted with primate collars to which actigraphy monitors were attached. Actigraphy recording was conducted during baseline conditions and following acute injections of vehicle, methadone (0.03 – 1.0 mg/kg, i.m.), buprenorphine (0.01 – 1.0 mg/kg, i.m.) or naltrexone (0.03 – 1.0 mg/kg, i.m.) in the morning (10h, 4h after "lights on") or in the evening (16:30h, 1.5h before "lights off"). Results: Morning treatment with methadone or buprenorphine dose-dependently impaired sleep in rhesus monkeys, with at least one dose significantly increasing sleep latency and decreasing sleep efficiency. Evening treatment with methadone or buprenorphine also impaired sleep, with lower doses significantly inducing sleep alterations compared to morning treatments. The effects of buprenorphine on sleep was a biphasic function, with the highest doses not disrupting sleep. Treatment with naltrexone significantly improved sleep-like measures in rhesus monkeys, with evening treatments improving measures of both sleep latency and sleep efficiency. Conclusion: Acute administration of methadone and buprenorphine induced marked sleep impairment in rhesus monkeys, even when the drugs were administered in the morning. Unexpectedly, acute administration of the opioid antagonist naltrexone significantly improved sleep-like measures. Our findings show that the currently available pharmacotherapies for OUD significantly affect sleep in naïve monkeys, and that opioid mechanisms yet to be determined may play a significant role in sleep-wake regulation. Support (if any): Supported by NIH grants DA049886 to L.F.B.; DA048586 to C.A.Z.; DA039167 to K.B.F.; DA011792, DA043204 and DA046778 to J.K.R..